IMPLEMENTATION OF GREEN ACCOUNTING, INTELLECTUAL CAPITAL AND ENVIRONMENTAL PERFORMANCE ON COMPANY VALUE MEDIATED BY FINANCIAL PERFORMANCE - Widiyaningsih, Vitalis Ari; Nugroho Jati, Agustinus Kismet (Jurnal Akuntansi Bisnis, 2024)
Background: Company value is not only influenced by investment fundamentals and business expansion, but also by environmental factors and society is increasingly complex. This research looks at green practices accounting as strategy For increase efficiency management environment And importance not quite enough answer social And environment companies, especially in the mining sector, often receive critics.Objective: Objective from study This is Forknow influence green     accounting, intellectual capital and performance environment to Mark Company. Variable Mediation that is Performance Finance Also will tested whether it will strengthen the influence of Green Accounting , Intellectual Capital And Performance Environment encountered Mark Company.Method Study : Method Which used study This that is method quantitative with data secondary. Technique collection data that is using purposive sampling . The data used is in the form of reports annual financials for mining companies listed on the IDX 2018 period - 2022 and get research sample as much 35. Method study This use model regression data panel with test three models namely common effect model , fixed effect model and random effect model with tool test Eviews 11.Results Study : Results study show Green Accounting , Intellectual Capital And Performance Environment No influential significant to Mark Company. Performance Company influential significant to Mark Company. Performance company No mediate influence Green Accounting against mark company. Performance Company mediate the influence of environmental performance on company value. Company performance does not mediate the influence of Intellectual Capital on Company Value.Authenticity/Novelty Study : Study This take variable Which different that is Green Accounting Which moment This the more in intensify related damage natural Which happen No Because public general but Also the impact of business processes, research data is a mining company Which registered in BEI period 2018 - 2022